LONELINESS AND YOUNG PEOPLE EXPERIENCING MENTAL HEALTH DIFFICULTIES: EVIDENCE AND FURTHER RESEARCH - Placa, Vincent La; Oham, Charles (PEOPLE: International Journal of Social Sciences, 2019)
This article reviews the current evidence base around loneliness; mental health, and young people, and the challenges identified in conducting research in this area. It then proceeds to consider the scope of further research and its impact upon policy and practice; in terms of inclusion of more enhanced theoretical frameworks; use of qualitative research and methodologies and impact of research upon policy and practice and enablement of more effective policies and interventions.